The new noninvasive occlusion spectroscopy hemoglobin measurement method: a reliable and easy anemia screening test for blood donors. Issue 4 (15th July 2012) - Pinto, Márcio; Barjas‐Castro, Maria Lourdes; Nascimento, Simone; Falconi, Mônica Almeida; Zulli, Roberto; Castro, Vagner
<x xml:space="preserve">Abstract</x> BACKGROUND: The tests used for anemia screening in blood donors are based on fingerstick samples, leading to discomfort and complaints. The aim of this study was to analyze the feasibility of occlusion spectroscopy method in blood banks and to compare the method with fingerstick hemoglobinometer and hemoglobin (Hb) determination on an automatic blood analyzer. STUDY DESIGN AND METHODS: The study enrolled 205 consecutive volunteer blood donors. Samples were collected by fingerstick and venous punction to determine Hb level by a Hemocue Hb201+ (Hb‐F) and automatic blood analyzer (Hb‐V) and compare to the noninvasive Hb determination by occlusion spectroscopy using NBM200 system (Hb‐NI). The percentage errors of Hb‐F and Hb‐NI of all donors as well as stratified by sex, weight, and age levels were compared to Hb‐V as reference values using Wilcoxon signed rank test. RESULTS: The results obtained with Hb‐F showed significant errors (p < 0.001) in the general group as well as when stratified by sex, weight, and age groups, above values obtained with Hb‐V. Hb‐NI showed significant errors only in females (p = 0.026) and weight level of 61 to 70 kg (p = 0.034), below Hb‐V values. CONCLUSIONS: Hb‐NI seems to be a good method in terms of precision and feasibility for anemia screening of blood donors as well as being much more comfortable for donors.